2018
DOI: 10.1017/jrc.2018.9
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies of Disabled People in Residential Environments after Injury Events

Abstract: The study explored the lived experiences of people with injury events in their residential environment. Participants were 65 people with disabilities and chronic diseases in Sweden with residential living injuries (females = 40 (61.5%), men = 25 (38.5%), age range 20–90 year old). They completed qualitative interviews on their experiences of injury events in their residential environment. Thematic analysis of the data yielded evidence to suggest the following issues: (1) individual coping resource preferences;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
3
4
0
Order By: Relevance
“…This backs up a previous study on injuries conducted in Australia [17] which stated that walking up or down stairs without handles is difficult; even with handles, some stairs are difficult to use due to their steepness. This resemblance could be due to the fact that physical infrastructure faces the same challenges everywhere.…”
Section: Plos Onesupporting
confidence: 52%
“…This backs up a previous study on injuries conducted in Australia [17] which stated that walking up or down stairs without handles is difficult; even with handles, some stairs are difficult to use due to their steepness. This resemblance could be due to the fact that physical infrastructure faces the same challenges everywhere.…”
Section: Plos Onesupporting
confidence: 52%
“…When accidents occur at home and in the residential care-settings, affected individuals can use various coping strategies in their daily life and living situation (Lundälv, 2018d). The injured parties or those who have witnessed an accident may also talk about the incident with family, friends and others.…”
Section: Discussionmentioning
confidence: 99%
“…Research has also brought attention to the experiences of residents and family members concerning implemented home modifications (Cumming et al, 1999;Hawkins and Stewart, 2002;Petersson et al, 2009;Kruse et al, 2010;Aplin et al, 2015;Norin et al, 2017;Pettersson et al, 2017;Thodelius and Lundälv, 2018). There is also need for additional research regarding living conditions at various institutions (Thodelius et al, 2017a(Thodelius et al, , 2017bLundälv, 2018a;Lundälv, 2018b) and research has indicated a need for social support for people who have been injured (Lundälv, 2018c;Lundälv, 2018d). Previous studies have also focusing on, for example, the situations and health for elderly persons, building design for people with dementia and inclusive design of open space and safety for visually impaired persons (Leung et al, 2013;Fisher et al, 2018;Siu et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is important to be able to change perspective and work intersubjectively, and hospital social workers need to set aside time for patients to talk about risks and injury events in the residential environment. Along these lines, it is equally important to discuss experiences of "near-risk situations" and coping strategies (Lundälv, 2018). Letting patients with visual impairments talk about their experiences during visits with hospital social workers can help both the patient and others in the same situation, by extending patients' and professionals' knowledge of situations and useful strategies.…”
Section: Risks and Injury Events In Residential Settingsmentioning
confidence: 99%
“…Even if these support systems are institutionalized in the welfare context, however, previous research has found that individuals with different disabilities and impairments perceived social workers as untrustworthy, mainly because they felt that the social workers had not paid attention to them and their story (Lundälv, 2018). A study found that social workers are stressed and seldom have time to listen to patients' stories about accidents, but also that people with visual impairments sometimes did not want to talk about accidents, since they wanted to be able to move on from the incidents (Lundälv, 2018, p. 93). Consequently, it is not only the institutionalization of the professional role that is of importance but also the concept of trustful dialogues (Buber, 1970; Erikson, 1950; Hanssen, 2007).…”
Section: Aim and Research Questionsmentioning
confidence: 99%